2012
DOI: 10.1002/pd.3943
|View full text |Cite
|
Sign up to set email alerts
|

Detection rates of clinically significant genomic alterations by microarray analysis for specific anomalies detected by ultrasound

Abstract: ObjectiveThe aim of this study is to understand the diagnostic utility of comparative genomic hybridization (CGH)-based microarrays for pregnancies with abnormal ultrasound findings.MethodsWe performed a retrospective analysis of 2858 pregnancies with abnormal ultrasounds and normal karyotypes (when performed) tested in our laboratory using CGH microarrays targeted to known chromosomal syndromes with later versions providing backbone coverage of the entire genome. Abnormalities were stratified according to org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
220
19
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(274 citation statements)
references
References 32 publications
(46 reference statements)
32
220
19
3
Order By: Relevance
“…Our data show that at least 4.7% of patients with 1 or more fetal structural abnormalities have a clinically significant microarray abnormality that would have been missed by karyotype analysis, similar to previous reports 3, 5, 6, 7. Additionally, at least 2.5% of patients whose indication did not include a structural fetal abnormality had a CSCA detected by CMA that would have been missed by karyotyping alone.…”
Section: Discussionsupporting
confidence: 89%
“…Our data show that at least 4.7% of patients with 1 or more fetal structural abnormalities have a clinically significant microarray abnormality that would have been missed by karyotype analysis, similar to previous reports 3, 5, 6, 7. Additionally, at least 2.5% of patients whose indication did not include a structural fetal abnormality had a CSCA detected by CMA that would have been missed by karyotyping alone.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study showed that microarray analysis detected clinically significant CNVs,~75% of which were smaller than 10 Mb, in up to 6.5% of fetuses with an ultrasound abnormality and normal karyotype. 2 No comprehensive data currently give the true incidence of pathogenic CNVs < 6 Mb, and thus it is difficult to determine exactly what proportion of CNVs would be missed, but it is clear that a significant number would not be detected. Comparing the efficacy of the different diagnostic techniques and determining the limits of detection would require a very large prospective study comparing NIPT and microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Over the same time period, there has been a move to replace traditional karyotyping following invasive testing with microarray analysis 9 , which increases detection of pathogenic chromosomal rearrangements to include microdeletion and microduplication syndromes. 1,2,4 There are concerns that widespread implementation of NIPT stands to decrease the detection of these other pathogenic rearrangements. 10 However, in principle, sequencing of cfDNA can also be used for detecting other unbalanced chromosomal rearrangements prenatally, and a number of proof-of-concept studies using a variety of sequencing depths and bioinformatics approaches have detected a range of fetal subchromosomal abnormalities in maternal plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetuses with ultrasound abnormalities are known to carry not only the highest percentage of microscopically visible chromosome abnormalities 1-3 but also submicroscopic aberrations. [4][5][6][7][8][9][10][11] Before array implementation, these submicroscopic chromosome aberrations could only be detected if targeted testing was requested in case of specific ultrasound anomalies, for example, 22q11 deletion in fetuses with cardiac defects. 12 However, based on prenatal phenotyping by ultrasound examination, it is not always easy to obtain a clinical diagnosis and to determine which locus/loci should be investigated.…”
Section: Introductionmentioning
confidence: 99%